Mechanical analysis of the vascularized fibular graft prosthetic composite (VFGPC) for internal hemipelvectomy reconstruction. Issue 7 (22nd May 2017) - Morris, Jonathan; Yang, Rui; Roth, Michael; Gill, Jonathan; Gorlick, Richard; Lo, Yungtai; Hoang, Bang H.; Garfein, Evan; Geller, David S.
Abstract : INTRODUCTION: The vascularized fibular graft prosthetic composite (VFGPC) is used for reconstruction after internal hemipelvectomy. The purpose of this study was to create a mathematical model that calculates the mechanical effects of the vascularized fibular graft on the VFGPC. METHODS: The effects of the VFG positioning were calculated based on three‐dimensional static analyzes to determine the direction, magnitude, and distribution of the forces through the prosthesis and VFG. The shear stress (SS) and cyclic loads to failure (CLF) were calculated. By varying the location of the VFG on the sacrum the zone of acceptable placement was calculated. RESULTS: Utilization of the VFG decreased the forces through the implant by 15‐35% and decreased SS 20‐54%, depending on stance. The CLF improved by 94%. The zone of acceptable placement for the VFG was found to be between 0° and 15° of the vertical axis in the sagittal plane and 0° and 30° of the posterior axis in coronal plane. CONCLUSION: Determining the position of the VFG pre‐operatively allows for the creation of a customized cutting jig can be utilized to create graft allowing for accurate fibular osteotomies, minimization of ischemia time, and decreased intra‐operative handling of the graft.